Bleeding gastric and duodenal ulcers: case-control study comparing angioembolization and surgery. (4th May 2017) - Nykänen, Taina; Peltola, Erno; Kylänpää, Leena; Udd, Marianne
Abstract: Objectives: To compare the safety, efficacy and feasibility of transcatheter arterial embolization (TAE) and surgery in the treatment of bleeding gastric and duodenal ulcers (BGDUs). Materials and methods: The study group comprised patients receiving TAE or surgery for BGDUs after failed endoscopic hemostasis in Helsinki University Hospital (HUH) during 2000–2015. Hospital medical records provided study data. 30-d mortality and rebleeding rates were the primary outcomes. Postoperative complications, blood transfusion rate, and the durations of intensive care and hospital admissions were the secondary outcomes. Results: During the study period, BGDUs lead to 1583 hospital admissions. TAE or surgery was necessary on 85 (5.4%) patients, 43 receiving surgery and 42 TAE. Out of 42, 16 received prophylactic TAE. Two underwent angiography and TAE to localize the bleeding. The remaining 24 received TAE for active or recurrent bleeding after endoscopy. The comparison of TAE ( n  = 24) and surgery ( n  = 43) included only patients with active or recurrent bleeding. Mortality rate was 12.5% after TAE and 25.6% after surgery ( p  = 0.347). Rebleeding rate was 25% after TAE and 16.3% after surgery ( p  = 0.641). Postprocedural complications were less frequent after TAE than surgery (37.5 vs. 67.4%, p  = 0.018). Other secondary outcomes did not differ. Out of 85 procedures, 14 (16.5%) took place between midnight and 8 a.m., all nighttime interventions being surgeries. Conclusions: Mortality and rebleeding rates did not differ between TAE and surgery. With less postoperative complications, TAE should be the preferred hemostatic method when endoscopy fails.